2006
DOI: 10.1136/bmj.38751.597963.ae
|View full text |Cite
|
Sign up to set email alerts
|

Does amblyopia affect educational, health, and social outcomes? Findings from 1958 British birth cohort

Abstract: Objective To determine any association of amblyopia with diverse educational, health, and social outcomes in order to inform current debate about population screening for this condition. Design, setting, and participants Comparison of 8432 people with normal vision in each eye with 429 (4.8%) people with amblyopia (childhood unilateral reduced acuity when tested with correction and unaccounted for by eye disease) from the 1958 British birth cohort, with respect to subsequent health and social functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 19 publications
6
95
0
3
Order By: Relevance
“…However, fewer people with amblyopia were found to have completed higher university degrees. This finding was supported by Rahi et al 59 who reported upon findings of the 1958 British birth cohort with respect to any association of amblyopia with diverse educational, health and social outcomes. The authors could find no statistical evidence between the presence of amblyopia and educational attainment or paid employment.…”
Section: Impact Of Amblyopia Upon Educationsupporting
confidence: 76%
See 1 more Smart Citation
“…However, fewer people with amblyopia were found to have completed higher university degrees. This finding was supported by Rahi et al 59 who reported upon findings of the 1958 British birth cohort with respect to any association of amblyopia with diverse educational, health and social outcomes. The authors could find no statistical evidence between the presence of amblyopia and educational attainment or paid employment.…”
Section: Impact Of Amblyopia Upon Educationsupporting
confidence: 76%
“…Rahi et al 59 reported that adults with amblyopia were no more likely to be bullied (either at the age of 7 or 11 years); and could find no evidence for an association between the presence of amblyopia and participation in social activities in either childhood or adult life. The authors also stated that those with amblyopia were no more likely to report depression or psychological distress in adult life.…”
Section: Emotional Well-being and Amblyopiamentioning
confidence: 99%
“…1% of the population [1]. Rahi recently could not detect a functionally or socially significant decrease in the quality of life of amblyopes as based on gross outcomes of quality of life, like educational achievement, employment, and socioeconomic achievement [2]. Such decrease can, however, be detected at the level of daily functional restrictions in amblyopia patients.…”
Section: Introductionmentioning
confidence: 97%
“…Studies have found no difference in occupational class, educational attainment, employment or general and mental health between those with amblyopia and those without it. 18,19 Nevertheless vision screening programmes are commonplace and it is therefore important to evaluate the existing service.…”
Section: Discussionmentioning
confidence: 99%